Milk Polar Lipids Reduce Atherogenic Lipoprotein Cholesterol and Attenuate Atherosclerosis Development in LDL-Receptor Knockout Mice Fed a Western-Type Diet (P06-051-19). (13th June 2019) - Millar, Courtney; Jiang, Christina; Norris, Gregory; Blesso, Christopher
Abstract: Objectives: Purified milk sphingomyelin (SM), a polar lipid (PL) component of milk fat globule membranes, is protective against dyslipidemia in high-fat, diet-fed mice. However, it is unclear whether ingestion of the total milk PL fraction can have similar hypolipidemic effects as purified SM, and if this confers protection from inflammation and atherosclerosis. To determine this, LDLr -/- mice were fed high-fat, high-cholesterol diets with and without added milk PL from butter serum, a dairy co-product rich in PLs and SM. Methods: Male LDLr -/- mice (age 6 weeks) were fed ad libitum either a high-fat, high-cholesterol diet (CTL; 45% kcal from fat, 0.22% cholesterol added by weight; n = 15), or the same diet supplemented with 1% milk PL (1% MPL; n = 15) or 2% milk PL (2% MPL; n = 15) added by weight from butter serum. All diets were adjusted to match in energy density, macronutrient composition, and calcium content. After 14 weeks on diets, mice were fasted for 6 hours prior to blood and tissue collection/processing at sacrifice. Results: Supplementation with 2% MPL significantly reduced serum cholesterol (−51%) compared to CTL (p < 0.01), with fast protein liquid chromatography (FPLC) showing dose-dependent effects in lowering VLDL- and LDL-cholesterol. Serum CCL2 was 56% lower in 2% MPL compared to CTL ( p < 0.05). No other significant differences were found in serum markers of inflammation or insulin resistance. Compared to CTL, 2% MPL-fed mice had significantly lower mRNA expression of Scd1 and Mip1b in liver, and Ccl2 in epididymal adipose tissue (p < 0.05). Notably, milk PL dose-dependently reduced atherosclerosis development in thoracic aorta, with 2% MPL significantly lowering neutral lipid plaque size by 59% (p < 0.01). Ccl2 mRNA expression was also significantly reduced by 67% in the descending aorta with 2% MPL (p < 0.05). Conclusions: Milk PL strongly reduced atherogenic lipoprotein cholesterol in LDLr -/- mice fed a Western-type diet, and modestly lowered inflammatory markers in the serum, liver, adipose, and aorta. These factors likely contributed to the strong reduction in atherosclerosis development in thoracic aorta seen with 2% MPL. Milk PL content may be important to consider when choosing dairy products as food. Funding Sources: This work was supported by a research grant to C. Blesso from the National Dairy Council.